The perception of women regarding the signs and symptoms of the climate/menopause and their relationship with the quality of life (Research, Society and Development, 2022)
The transition from the reproductive to the non-reproductive period characterizes the climacteric/menopause, starting around the age of 35 and extending around the age of 60 years. The aim of this study is to describe the relationship between the signs and symptoms of menopause/menopause with the quality of life of women attending a Basic Health Unit. The research is descriptive and exploratory. Opinion Number: 2,634,860 and CAAE: 86378818.1.0000.5349. The population consisted of women aged between 40 and 60 years or more, with a sample of 205 women, in the city of Canoas, RS. The selection process will be a probabilistic sampling of the intentional type. There were three instruments for the collection: the characterization of the sample with sociodemographic data; the validated questionnaire, the Menopause Rating Scale (MRS), characterizes the signs and symptoms of menopause/menopause; the Brazilian Version of the Quality of Life Questionnaire-SF-36, assesses the quality of life of women in relation to their current situation, comprising four domains: Physical, Psychological, Social Relations and Environment. Menopause women present moderate to very severe signs and symptoms, when the association between the MRS and the SF-36 instrument was performed, there was a direct association with a reduction in quality of life. In view of the arguments, it was possible to see that the climacteric/menopause phase compromises the quality of life of women; build well-designed public policies so that health professionals can be prepared to identify and guide women in this period. With this, it is possible to contribute to promoting the care of women in menopause/menopause, since most of them are heads of families and need to remain productive.